A cross-sectional comparison of different resistance training techniques in the squat exercise - Egan, A. (UW-L Journal of Undergraduate Research, 2004)
The purpose of this study was to compare the perceived exertion, force and power characteristics of different resistance training techniques in the squat exercise. These techniques included traditional resistance training, super slow, and maximal power training. Fourteen women completed three experimental trials in a randomized crossover design. The traditional resistance training protocol consisted of six sets of six repetitions using 80% of 1RM. The super slow protocol consisted of six sets of six repetitions using 55% of1RM. The maximal power protocol consisted of 6 sets of six repetitions using 30% of 1RM. Rating of perceived exertion (RPE) measures were obtained following each set. Also, a session RPE value was obtained 30 minutes following each exercise session. The peak performance system was used to collect kinematical data (peak power, peak force, bar velocity). When comparing average RPE and session RPE, no significant differences were found. Power training had significantly lower (P<0.05) average and session RPE (4.9±1.9 and 4.50±2.1) compared to both super slow training (7.81±1.75 and 7.43±1.73) and traditional training (7.33±1.52 and 7.13±1.73). Comparing the mechanical data showed that the maximum force, maximum velocity and maximum power for the super slow training was significantly less then that of both the power training and traditional training (P<0.05). Although the subjects perceived the super slow training to be more difficult than power training, the kinematic data suggests that this is not the most appropriate method for maximizing peak power, force and velocity.